Pengaruh Olahraga Terhadap Kemampuan Motorik Kasar Anak Usia Sekolah Dasar - Anggita Uli Angel Gultom; Desi Sri Kelengna Surbakti; Nadhilah Nazwa; Dini Syarafina; Fajar Siddik (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Based on observations at SDN 067245. Education is the most important component in advancing a country, and no aspect of life can be separated from the role of education. (Mustadi, 2018) In this case, the parts of education which include educators, students, curriculum, educational environment, facilities and sources of learning tools must support each other to achieve educational goals. Sport plays an important role in supporting the development of gross motor skills in elementary school-aged children. Regular physical activity can help improve a child's strength, coordination, agility and balance. Apart from that, exercise can also improve children's cardiovascular health, physical fitness and self-confidence. The type of research used by researchers is Qualitative Research. Where the data collection instruments used are in the form of observation sheets, questionnaires, interviews and field notes.